PENGARUH PERENDAMAN GIGI PADA KITOSAN SISIK IKAN HARUAN (Channa striata) TERHADAP PELEPASAN FOSFAT - Muhammad Hafly Fariz Asyraq; Deby Kania Tri Putri; Tri Nurrahman; Agung Satria Wardhana; Bambang Setiawan (Dentin, 2024)
Background: Chitosan solution from Haruan fish scales (Channa striata) can be used to maintain tooth enamel structure by reducing the rate of solubility of hydroxyapatite or tooth demineralization under acidic conditions. Chitosan haruan fish scale (Channa striata) has the potential to be an anti-demineralization agent. Objective: Analyze the effect of immersing teeth in chitosan solution of 2.5% and 5% Haruan fish scales (Channa striata) on levels of phosphate release. Method: This study used the true experimental method with a posttest-only control group design consisting of 3 treatment groups, namely the negative control, the 2.5% group and the 5% group. All groups were immersed in lactic acid solution pH 5.2. Measurement of phosphate release levels using a uv-vis spectrophotometer. Results: The results of the One Way Analysis of Variance (ANOVA) test obtained a value of p = 0.00 <0.05 which indicated that the hypothesis was accepted or that there was an effect of soaking the teeth in chitosan solution of Haruan fish scales (Channa striata) with a concentration of 2.5% and 5% on phosphate release . The Bonferroni Post Hoc Test showed that there were significant differences in all groups, namely the negative control group with the 2.5% and 5% groups, the 2.5% group and the 5% group. Conclusion: Chitosan from Haruan fish scales (Channa striata) concentrations of 2.5% and 5% are able to inhibit phosphate release on teeth and have the potential as alternative biomaterials in inhibiting tooth demineralization.Keywords: Caries, Chitosan, Demineralization, Haruan, Phosphate